Enterprise Architecture Planning with TOGAF ADM: A Case Study of a Heavy Equipment Rental Service Company - Rian Safrianto (Applied Information System and Management (AISM), 2025)
Strategic Information Systems (IS) and Information Technology (IT) planning play a vital role in aligning technological initiatives with business objectives, particularly in asset-intensive industries. This study aims to implement the TOGAF ADM framework to design a strategic IS/IT planning model for a heavy equipment rental company, demonstrating how enterprise architecture can align IT initiatives with business goals. PT. XYZ has not yet implemented an information system strategy for the company’s needs in terms of management, leading to inefficiencies in business operations at PT. XYZ. A qualitative approach was used to obtained through in-depth interviews with company’s owners and managers,  observation data of company’s IT asset also collected to describe organization’s current IS/IT landscape and applies the TOGAF ADM phases to design an enterprise architecture that supports business-IT alignment. This study demonstrates how TOGAF ADM can provide a structured methodology for identifying business needs, defining architectural visions, and developing a roadmap for IS/IT improvements. Findings indicate that using EA frameworks such as TOGAF ADM enhances strategic planning capabilities, supports organizational agility, and provides a repeatable model for similar enterprises in the rental or industrial sector. The results offer valuable insights for practitioners and researchers interested in applying enterprise architecture to improve IS/IT strategic planning processes.